2015
DOI: 10.1007/s12149-015-0946-x
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid adenoma upstaging the lung cancer

Abstract: Mediastinal staging of NSCLC with noninvasive methods such as PET/CT can be misleading when a mediastinal disease accompany. Histopathologic confirmation should be made before any treatment plan. Herein, we presented a case of parathyroid adenoma upstaging the lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The frozen section result was compatible with a parathyroid adenoma and the patient underwent right thoracotomy upper bilobectomy for lung carsinom. [7] An adenoma was localized in the anterior mediastinum in seven patients and in the middle mediastinum in four patients. The mean diameter calculated by taking into account the longest diameter of parathyroid adenomas was 21.1 mm.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The frozen section result was compatible with a parathyroid adenoma and the patient underwent right thoracotomy upper bilobectomy for lung carsinom. [7] An adenoma was localized in the anterior mediastinum in seven patients and in the middle mediastinum in four patients. The mean diameter calculated by taking into account the longest diameter of parathyroid adenomas was 21.1 mm.…”
Section: Resultsmentioning
confidence: 96%
“…[9,10] Today, parathyroidectomy with VATS and RATS provides certain advantages such as less postoperative pain, less complications, shorter hospitalization time, shorter time to return to daily activities, and improved cosmetic results. Thoracoscopic approach was first established in 1994 by Prinz et al [7] and it has become a commonly used method for the excision of mediastinal parathyroid adenomas today. Alesina et al [11] reported that the mean operation time was 90±53 min in seven patients who underwent thoracoscopy for mediastinal parathyroid adenoma and all procedures were completed thoracoscopically.…”
Section: Discussionmentioning
confidence: 99%